ChemInform Abstract: A Highly Efficient One‐Pot Synthesis of Indenopyridine‐Fused Spirocyclic Systems. Issue 28 (June 2016) - Shakibaei, Ghazaleh Imani; Bazgir, Ayoob
Abstract: The title compounds are obtained by environmentally‐friendly one‐pot multi‐component reaction of indanone (I), isatins, and malononitrile in the presence of a range of amines.